Cannabis sativa (Linnaeus, 1753): The use of its extract against Rhipicephalus linnaei (Audouin, 1826) ticks - Camargo-Mathias, Maria Izabel [UNESP]; de Lima Rodrigues, Milena [UNESP]; da Silva, Odaiza [UNESP]; de Abreu, Marina Rodrigues [UNESP]; Sapatini, Davy [UNESP] (Elsevier, 2024)
To minimize the damage caused by synthetic acaricides to non-target organisms, the use of bioactives compounds extracted from plants has been considered. In this study, semi-engorged females of Rhipicephalus linnaei ticks were exposed to Cannabis sativa flower extract (submersion for 5 minutes in different concentrations diluted in ethanol 30 %) evaluated alterations in the integument and salivary glands. The results demonstrated that lower concentrations of the extract caused damage to both the integument and salivary glands, affecting the cuticular epithelial cells responsible for synthesizing all layers of the cuticle. The concentration of 2.5 mg/mL caused more extensive damage than 5.0 mg/mL, and 40 mg/mL completely disrupted the epithelium. Exposure of the salivary glands showed that at 2.5 ug/mL dose the glandular acini was disrupted, leaving only a heterogeneous mass with some nuclei of acinar cells, leading to acinar rupture. These findings indicate that the extract from Cannabis sativa flowers irreversibly alters the morphology and consequently, interferes with the functionality of different vital organs.